The Little foxes - Wyler, William 1902-1981 (MGM Home Entertainment, 1941)
It's the turn of the century in the deep South, and the Hubbard siblings are embroiled in their money-driven, power-hungry civil war. Most calculating of the group id Regina, who along with her brothers, demands ownership of a cotton mill expected to yield millions. Proving that blood is not thicker than greed, the Hubbards will stop at nothing to push their unscrupulous deal through...even if it means destroying everyone around them.